How Narratives Are Shaping AI Law and Policy - Claire Boine (Washington University Journal of Law and Policy, 2026)
Narratives shape reality, foreign policy, and the technologies societies build. This Essay argues that stories are not peripheral to Artificial Intelligence (AI) governance, they are central drivers of transnational AI law and policy. Through case studies, it shows how narratives structure legal and political response to AI. Whether the narrative is Sputnik’s launch as the precursor to America’s own journey to space, or competing beliefs about what AI is, the stories policymakers tell themselves about AI determine what falls inside and outside the regulatory framework. Narrative choice is in itself a form of governance.
Keywords: #AIandNarratives; #Geopolitics; #EUsAIAct; #ScalingLaws; #AIPolicyMaking